Program Pemeriksaan Kesehatan Lansia di Lingkungan Songkolo Kelurahan Borongloe Kecamatan Bontomarannu - Agus, Al. Ihksan; Fitriani, Fitriani; Nisa, Khairun (PT.Mantaya Idea Batara, 2023)
Basically obtaining health is a basic right for everyone regardless of the economic and social status of the community itself. However, in practice, health services for the community still encounter many obstacles. Health services have not been able to reach all the general public in accessing information related to health issues is still very difficult Community service in the form of social health checks for the elderly is a desire and dream that we have plan. The purpose of this service is to provide information and health services directly to the community. The method of implementing community service with direct counseling techniques to the community. The results of the service, the elderly can improve their health and productivity so as not to aggravate the condition, besides that with this activity the elderly can exchange ideas with one another. The conclusion of this service is the importance of continuous education and socialization to the community regarding health, increasing awareness of the elderly to always maintain their health with routine controls both at the puskesmas and posyandu.